Plasma‐based ambient mass spectrometry techniques: The current status and future prospective. Issue 4 (13th December 2013) - Ding, Xuelu; Duan, Yixiang
<x xml:space="preserve">Abstract</x> Plasma‐based ambient mass spectrometry is emerging as a frontier technology for direct analysis of sample that employs low‐energy plasma as the ionization reagent. The versatile sources of ambient mass spectrometry (MS) can be classified according to the plasma formation approaches; namely, corona discharge, glow discharge, dielectric barrier discharge, and microwave‐induced discharge. These techniques allow pretreatment‐free detection of samples, ranging from biological materials (e.g., flies, bacteria, plants, tissues, peptides, metabolites, and lipids) to pharmaceuticals, food‐stuffs, polymers, chemical warfare reagents, and daily‐use chemicals. In most cases, plasma‐based ambient MS performs well as a qualitative tool and as an analyzer for semi‐quantitation. Herein, we provide an overview of the key concepts, mechanisms, and applications of plasma‐based ambient MS techniques, and discuss the challenges and outlook. © 2013 Wiley Periodicals, Inc. Mass Spec Rev 34: 449–473, 2015.